2020
DOI: 10.1002/nur.22067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hospital nurses' internalized dominant values, organizational silence, horizontal violence, and organizational communication on patient safety

Abstract: Recent studies have identified common problems with patient safety in hospitals and medical institutions have responded, prioritizing service quality and performance, including patient safety. However, the factors influencing safety for hospital patients are still being examined and clarified. We aimed to investigate how hospital nurses' internalized dominant values, organizational silence, horizontal violence, and organizational communication satisfaction can affect patient safety and to construct and verify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…This is in accordance with another finding which stated that job satisfaction is influenced by communication satisfaction in an organization, which continues to increase in more professional staff along with rise in age. 18 The length of time a person has worked in a hospital and certain units indicates their ability to possess more experience working as nurses. Experience influences communication satisfaction, which supports the quality of speech.…”
Section: Resultsmentioning
confidence: 99%
“…This is in accordance with another finding which stated that job satisfaction is influenced by communication satisfaction in an organization, which continues to increase in more professional staff along with rise in age. 18 The length of time a person has worked in a hospital and certain units indicates their ability to possess more experience working as nurses. Experience influences communication satisfaction, which supports the quality of speech.…”
Section: Resultsmentioning
confidence: 99%
“…Purpora (2010) reported that horizontal violence among nurses affects patient safety via peer relationships. Doo and Kim (2020) suggested that the internalized predominant values of nurses affect patient safety with organisational silence, horizontal violence and organisational communication satisfaction being mediator variables.…”
Section: Introductionmentioning
confidence: 99%
“…It refers to intimidating behaviours among peers (Kaiser, 2017). Horizontal violence among nurses negatively affects relationships among nurses, job satisfaction (Purpora et al., 2015) and patient safety (Doo & Kim, 2020; Purpora, 2010). The most frequent perpetrators were staff nurses (Hopkinson et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although negative workplace behavior entails the actions of an individual or a group, organizational culture, workloads, and leadership styles have all been shown to affect its occurrence [10]. It has been suggested that organizations seeking to mitigate negative workplace behaviors should aim to improve organizational processes that inform the management of bullying, implement skills-based training in communication and conflict management, and aim to promote accountability, transparency, and respectful peer alliances [11,12]. In the literature, there is little evidence of effective strategies that have been implemented in acute care settings to address negative workplace behavior experienced by nurses [2,13].…”
Section: Introductionmentioning
confidence: 99%